2011
DOI: 10.3168/jds.2010-3331
|View full text |Cite
|
Sign up to set email alerts
|

Fat composition of organic and conventional retail milk in northeast England

Abstract: This study of UK retail milk identified highly significant variations in fat composition. The survey, conducted over 2 yr replicating summer and winter, sampled 22 brands, 10 of which indicated organic production systems. Results corroborate earlier farm-based findings considering fat composition of milk produced under conventional and organic management. Organic milk had higher concentrations of beneficial fatty acids (FA) than conventional milk, including total polyunsaturated fatty acids (PUFA; 39.4 vs. 31.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
152
8
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(200 citation statements)
references
References 47 publications
35
152
8
5
Order By: Relevance
“…This suggested that the addition of between 1.6 and 2.1 kg of rolled oilseeds/cow per day to winter diets for conventional and organic cows, as in this study, would not affect milk production or total solids; the two parameters dairy producers are currently paid for. Across the experiments and production systems, linseed supplementation of silage diets during winter housing: (a) decreased the milk concentrations of SFA, C12:0, C14:0 and C16:0 and (b) increased milk concentrations of a range of nutritionally desirable FA (including MUFA, OA, VA, PUFA, n-3, ALA and RA) and the n-3/n-6 ratio, to levels similar to or higher than those found in milk from grazing (Butler et al, 2008(Butler et al, , 2011, being in line with previous studies (Akraim, Nicot, Juaneda, & Enjalbert, 2007;Collomb et al, 2004). On the other hand, linseed supplementation reduced concentrations of long chain n-3 (EPA and DPA) in Experiment 2, conforming to a recent meta-analysis citing a range of studies in which linseed and other oil supplements decreased concentrations of long chain (>18 C) unsaturated FA (Glasser et al, 2008).…”
Section: Conventional (C1)mentioning
confidence: 99%
See 3 more Smart Citations
“…This suggested that the addition of between 1.6 and 2.1 kg of rolled oilseeds/cow per day to winter diets for conventional and organic cows, as in this study, would not affect milk production or total solids; the two parameters dairy producers are currently paid for. Across the experiments and production systems, linseed supplementation of silage diets during winter housing: (a) decreased the milk concentrations of SFA, C12:0, C14:0 and C16:0 and (b) increased milk concentrations of a range of nutritionally desirable FA (including MUFA, OA, VA, PUFA, n-3, ALA and RA) and the n-3/n-6 ratio, to levels similar to or higher than those found in milk from grazing (Butler et al, 2008(Butler et al, , 2011, being in line with previous studies (Akraim, Nicot, Juaneda, & Enjalbert, 2007;Collomb et al, 2004). On the other hand, linseed supplementation reduced concentrations of long chain n-3 (EPA and DPA) in Experiment 2, conforming to a recent meta-analysis citing a range of studies in which linseed and other oil supplements decreased concentrations of long chain (>18 C) unsaturated FA (Glasser et al, 2008).…”
Section: Conventional (C1)mentioning
confidence: 99%
“…The method used for the FA analysis of milk samples in Experiment 1 was previously described by Butler et al (2011). An improved analytical method was used in Experiment 2, which was based on the methylation and esterification protocols for milk FA described by Chilliard, Martin, Rouel, and Doreau (2009).…”
Section: Milk Fatty Acid Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of comparative studies on the composition and properties of organic and conventional cows' milks. According to some authors, milk from organically certified systems contains more polyunsaturated fatty acids including n-3 polyunsaturated fatty acids and CLA (Ellis et al 2006;Bloksma et al 2008;Popović-Vranjes et al 2010;Butler et al 2011b), vitamins, and calcium (Bergamo et al 2003;Butler et al 2008). The more favourable fatty acids profile of organic milk in these studies has been mainly associated with organic diets richer in fresh grass and clover which conventional diets are based on silage and concentrates.…”
mentioning
confidence: 99%